Language Stylistics of ideologizing Means of man’s Image Actualization in the Ukrainian Soviet press 20-40s in the XX century (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
Verbal peculiarities of forming gender policy in Ukrainian mass-media in 20-40s of 20th century are analyzed taking into account ideologic canons and class approach which are typical for the press of the mentioned period.
Keywords: masculinity; gender policy; mass-media; discourse; soviet ideology; totalitarian society